FAKTOR PREDIKTOR LUARAN DISABILITAS PADA PASIEN STROKE ISKEMIK DI RUMAH SAKIT BETHESDA YOGYAKARTA - Irene Gracia Wijayanti; Rizaldy Taslim Pinzon; Esdras Ardi Pramudita (NEURONA, 2019)
PREDICTING FACTOR FOR DISABILITY OUTCOME IN PATIENT WITH ISCHEMIC STROKE IN BETHESDA HOSPITAL YOGYAKARTAABSTRACTIntroduction: It is estimated that around 25% to 74% of the 50 million stroke patients who live become independent either need the full or partial assistance due to decreased physical abilities, cognition, and emotions.Aims: The aim of this study is to measure the determinant factors for disability in patients with ischemic stroke.Methods: Cohort retrospective study using stroke registry and medical records on stroke patients in Bethesda Hospital, Yogyakarta, from 2015 to 2017. The inclusion criteria included patients ≥40 years old, that has been diagnosed with ischemic stroke using CT scan, had complete stroke registry data and medical record. For the analysis this study used univariate, Chi–square method for bivariate, and logistic regression method for multivariate analysis.Results: Based on multivariate analysis, muscle strength 0-4 (p=0.023), 3 (p=0.267), 2 (p=0.579), and 1 (p=0.049), 0 (p=0.003), also aphasia (p<0.001), dysphagia (p<0.001), and triglyceride levels (p=0.043) were significant predictors of disability outcomes in patients with ischemic stroke.Discussion: Motor strength, aphasia, dysphagia, and serum triglyceride were significant for disabillity outcome in patient with ischemic stroke.Keywords: Disability, outcome, ischemic strokeABSTRAKPendahuluan: Diperkirakan sampai saat ini sekitar 25% sampai 74% dari 50 juta pasien stroke yang hidup menjadi tidak mandiri baik membutuhkan bantuan seluruhnya atau hanya sebagian akibat penurunan kemampuan fisik, kognisi, dan emosi.Tujuan: Untuk mengetahui faktor yang berpengaruh pada luaran disabilitas pasien dengan stroke iskemik.Metode: Penelitian analitik secara retrospektif berdasarkan data stroke registry dan rekam medis pasien stroke iskemik di RS Bethesda, Yogyakarta, pada tahun 2015-2017. Kriteria inklusi adalah pasien berusia ≥40 tahun yang telah terdiagnosis dengan CT scan kepala, serta memiliki data stroke registry dan rekam medis yang lengkap. Analisis data univariat dan bivariat menggunakan metode Chi-square, serta multivariat dengan metode regresi logistik.Hasil: Berdasarkan hasil multivariat didapatkan bahwa kekuatan otot 0-4 (p=0,023), kekuatan otot 3 (p=0,267), kekuatan otot 2 (p=0,579), kekuatan otot 1 (p=0,049), kekuatan otot 0 (p=0,003), afasia (p<0,001), disfagia (p<0,001), dan kadar trigliserida (p=0,043) merupakan faktor prediktor yang signifikan terhadap luaran disabilitas pasien stroke iskemik.Diskusi: Kekuatan otot pasien saat masuk, gejala afasia, disfagia, dan kadar trigliserida berhubungan dengan luaran disabilitas pada pasien stroke iskemik.Kata kunci: Disabilitas, luaran, stroke iskemik